2020
DOI: 10.1128/aem.02919-19
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Whole-Genome Phylogeny of Animal, Environmental, and Human Strains Confirms the Genogroup Organization and Diversity of the Stenotrophomonas maltophilia Complex

Abstract: The Stenotrophomonas maltophilia complex (Smc) comprises opportunistic environmental Gram-negative bacilli responsible for a variety of infections in both humans and animals. Beyond its large genetic diversity, its genetic organization in genogroups was recently confirmed through the whole-genome sequencing of human and environmental strains. As they are poorly represented in these analyses, we sequenced the whole genomes of 93 animal strains to determine their genetic background and characteristics. Combining… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 29 publications
6
21
0
Order By: Relevance
“…The other genogroups with a significant number of isolates in our collection were #2 (19%), #3 (13%) and C (15%), which is in agreement with the frequency of isolates belonging to these groups in the worldwide population. In agreement with previous studies (Corlouer et al, 2017;Mercier-Darty et al, 2020), genogroup #2 represents the most genetically diverse group in our collection. As proposed by Gröschel et al (2020) and shown in Supplementary Table S1, the strains could be further classified into the monophyletic lineages named Sm1-Sm18 (termed S. maltophilia sensu lato) or the more distantly related lineages Sgn1-Sgn4 according to Vinuesa et al (2018).…”
Section: Classification Of S Maltophilia Isolates Into Genomic Groupssupporting
confidence: 93%
See 1 more Smart Citation
“…The other genogroups with a significant number of isolates in our collection were #2 (19%), #3 (13%) and C (15%), which is in agreement with the frequency of isolates belonging to these groups in the worldwide population. In agreement with previous studies (Corlouer et al, 2017;Mercier-Darty et al, 2020), genogroup #2 represents the most genetically diverse group in our collection. As proposed by Gröschel et al (2020) and shown in Supplementary Table S1, the strains could be further classified into the monophyletic lineages named Sm1-Sm18 (termed S. maltophilia sensu lato) or the more distantly related lineages Sgn1-Sgn4 according to Vinuesa et al (2018).…”
Section: Classification Of S Maltophilia Isolates Into Genomic Groupssupporting
confidence: 93%
“…Due to these large genetic divergences, and because previously proposed species are recognized to be closely related to S. maltophilia, it is increasingly accepted to present it as the S. maltophilia complex (Svensson-Stadler et al, 2012;Patil et al, 2018;Vinuesa et al, 2018). PCRbased multilocus sequence typing (MLST) and whole-genome sequencing (WGS) have clearly shown the existence of several genomic or phylogenetic groups in the S. maltophilia complex, and have helped to clarify the taxonomic status of the species (Hauben et al, 1999;Kaiser et al, 2009;Ochoa-Sánchez and Vinuesa, 2017;Steinmann et al, 2018;Gröschel et al, 2020;Mercier-Darty et al, 2020). Even strains isolated from the same patient (Pompilio et al, 2016;Chung et al, 2017) or patients within the same hospital (Valdezate et al, 2004) can belong to distant phylogenetic groups with different phenotypes, probably due to the emergence of adaptive mutations as a result of selective pressure in the clinical environment or inside the host.…”
Section: Introductionmentioning
confidence: 99%
“…Many S. maltophilia described that are responsible for a variety of infections in both humans and animals. By the comparative whole genome analysis of 375 unique S. maltophilia from various origins such as humans, other animals, and the environment, it was determined that bacteria originating from environment were distinct from those isolated from humans or other animals 38 . This indicates that RSB2 is unlikely to gain pathogenicity towards humans or other animals.…”
Section: Discussionmentioning
confidence: 99%
“…The genomic phylogeny of Sm was recently updated (Vinuesa et al, 2018 ) and S. maltophilia complex was defined, including Sm sensu stricto and several related genospecies. SM_CF is S. maltophilia sensu stricto through whole genome sequencing and phylogenomic analysis (Mercier-Darty et al, 2020 ). Both SM_REF and SM_CF belong to genogroup 6 (Hauben et al, 1999 ; Mercier-Darty et al, 2020 ), and no major difference in resistance genes was found.…”
Section: Methodsmentioning
confidence: 99%
“…SM_CF is S. maltophilia sensu stricto through whole genome sequencing and phylogenomic analysis (Mercier-Darty et al, 2020 ). Both SM_REF and SM_CF belong to genogroup 6 (Hauben et al, 1999 ; Mercier-Darty et al, 2020 ), and no major difference in resistance genes was found. Af strains were cultured on 2% malt agar containing 0.05% chloramphenicol at 37°C for 5 days.…”
Section: Methodsmentioning
confidence: 99%